Erectile Dysfunction Treatment Using Focused Linear Low-Intensity Extracorporeal Shockwaves: Single-Blind, Sham-Controlled, Randomized Clinical Trial - Sramkova, Tatjana; Motil, Igor; Jarkovsky, Jiří; Sramkova, Katerina (Urologia internationalis, 2020)
INTRODUCTION: Low-intensity extracorporeal shock wave therapy (Li-ESWT) is a new treatment modality for erectile dysfunction (ED). Our aim was to evaluate the treatment outcome of Li-ESWT for ED in single-blind, placebo controlled, randomized clinical trial. METHODS: Sixty patients were randomized into 2 age-matched groups: Group A - treatment and Group B - placebo. Treatment consisted of 4 sessions on the PiezoWave2 unit (R. Wolf and ELvation Medical). Effectiveness was assessed according to the International Index of Erectile Function 5 (IIEF-5), Erectile Hardness Score (EHS), questions 2 and 3 of the Sexual Encounter Profile (SEP 2, SEP 3), and Global Assessment Question (GAQ) scores at baseline and 4 and 12 weeks after treatment. We evaluated patient's and partner's subjective satisfaction. RESULTS: A statistically significant difference between the groups was found at 4 and 12 weeks after treatment with regard to the quality of erection as measured by the IIEF-5 (p = 0.049 and p < 0.001, respectively), the EHS after week 12 (p < 0.001), an increase in the EHS after 4 and 12 weeks (p = 0.030 and p < 0.001, respectively), after 12 weeks in GAQ (p < 0.001), SEP 2 (p = 0.05), SEP 3 (p < 0.001), and patient's satisfaction (p < 0.001) and partner's satisfaction (p < 0.001). CONCLUSIONS: The randomized single-blind study confirms that Li-ESWT significantly improves erectile function.
Keywords: jednoduchá slepá metoda; výsledek terapie; erektilní dysfunkce; Treatment Outcome; Extracorporeal Shockwave Therapy; Adult; Male; Single-Blind Method; Aged; lidé; dospělí; mužské pohlaví; senioři; léčba mimotělní rázovou vlnou; lidé středního věku; Humans; Erectile Dysfunction; Middle Aged